Cystic Bleb Management : A Case Report - Rachma, Adessa; Rifada, Maula (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Cystic Bleb Is An Abnormal Bleb Morphology Following Trabeculectomy Procedure. This Type Of Bleb Characterized By An Elevated, Thin, And Avascular Bleb Surface. Post-Operative Bleb Evaluation Needed To Be Done Thoroughly To Recognize And Prevent Further Complication Which Can Be Sight Threatening. Several Options Of Management Include Medical Therapy And Surgical Repair. To Report The Management Of Cystic Bleb. The Study Design Is A Case Report Study, Which Was Conducted At Indonesia National Eye Centre, Cicendo Eye Hospital, Bandung, Indonesia. Subject Of The Study Was A-17-Years-Old Female That Presented With Discomfort Sensation In The Right Eye, Which Previously Has Undergone Trabeculectomy Procedure With Antifibrotic Agent Application. Ophthalmological Examination Revealed A Cystic Bleb On The Right Eye. After Medical Therapy Was Given, The Symptoms Persist, Then The Cystic Bleb Was Surgically Repaired. Follow-Up Examination Showed An Improvement Of The Patient’s Condition, Measured By No Further Complaint Of Discomfort Sensation, A Good Bleb Morphology, And A Stable Intraocular Pressure. Cystic Bleb Is One Of The Complication From Trabeculectomy Which Could Progress To Devastating Condition. Surgical Treatment Is Indicated If Symptoms Persist After Medical Management, Or In The Presence Of A Bleb Leakage. Keywords: Antifibrotic, Cystic Bleb, Trabeculectomy